Trips Production in Khartoum State (University of Khartoum Engineering Journal, 2022)
The rapid increase in population, fast urbanization and change, high demand for public transport in Khartoum State necessitates development of a proper transportation plan for the state, to enable predicting the impacts that various policies and programs will have on travel. Travel demand forecasting is an essential part of the transportation planning process and trip production is the first step in the concept of four steps travel demand model. In this paper a model for trip production in Khartoum State is proposed. The trip generation model is based on data collected by the Ministry of Infrastructures and Transportation and a consultant in the period 2008-2011. The exclusion of incomplete data and outliers and the consideration of the car ownership in the development of the model, has resulted in a more realistic estimate of the number of trips produced than those predicted by the currently adopted model of Khartoum State. The results of this study predict the number of daily trips in the year 2035 at 9.56 million person-trips, creating a demand of 6.69 million person-trip/days to be covered by public transport. This will necessitate huge investments in mass transit systems to accommodate the uprising demand.